Compounds Involved in the Invasive Characteristics of Lantana camara - Hisashi Kato-Noguchi; Midori Kato (Molecules)
Lantana camara L. is native to tropical America and has naturalized in many other tropical, subtropical, and temperate regions in Asia, Africa, Oceania, North and South America, and Europe. L. camara infests diverse habitats with a wide range of climatic factors, and its population increases aggressively as one of the world’s 100 worst invasive alien species. Its infestation reduces species diversity and abundance in the natural ecosystems and reduces agricultural production. The life history characteristics of L. camara, such as its high reproductive ability and high adaptive ability to various environmental conditions, may contribute to its ability to infest and increase its population. Possible evidence of the compounds involved in the defense functions of L. camara against natural enemies, such as herbivore mammals and insects, parasitic nematodes, pathogenic fungi and bacteria, and the allelochemicals involved in its allelopathy against neighboring competitive plant species, have accumulated in the literature over three decades. Lantadenes A and B, oleanonic acid, and icterogenin are highly toxic to herbivore mammals, and β-humulene, isoledene, α-copaene thymol, and hexadecanoic acid have high insecticidal activity. β-Caryophyllene and cis-3-hexen-1-ol may function as herbivore-induced plant volatiles which are involved in sending warning signals to undamaged tissues and the next plants of the same species. Farnesol and farnesal may interrupt insect juvenile hormone biosynthesis and cause abnormal metamorphosis of insects. Several triterpenes, such as lantanolic acid, lantoic acid, pomolic acid, camarin, lantacin, camarinin, ursolic acid, and oleanonic acid, have demonstrated nematocidal activity. Lantadene A, β-caryophyllene, germacrene-D, β-curcumene, eicosapentaenoic acid, and loliolide may possess antimicrobial activity. Allelochemicals, such as caffeic acid, ferulic acid, salicylic acid, α-resorcylic acid, p-hydroxybenzoic acid, vanillic acid, unbelliferone, and quercetin, including lantadenes A and B and β-caryophyllene, suppress the germination and growth of neighboring plant species. These compounds may be involved in the defense functions and allelopathy and may contribute to L. camara’s ability to infest and to expand its population as an invasive plant species in new habitats. This is the first review to focus on how compounds enhance the invasive characteristics of L. camara.